Estimation of Generalized Entropy and Atkinson inequality indices from survey data - Martin Biewen; Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2003)
Applying a method suggested by Woodruff (Journal of the American Statistical Association, 1971), we derive the sampling variances of Generalized Entropy and Atkinson inequality indices when estimated from complex survey data. It turns out that this method also greatly simplifies the calculations for the i.i.d. case when compared to previous derivations in the literature. Both cases are illustrated with examples from the German Socio-Economic Panel Study and the British Household Panel Survey.
Keywords: 330